2022
DOI: 10.3389/fmicb.2022.811990
|View full text |Cite
|
Sign up to set email alerts
|

Habitats Show More Impacts Than Host Species in Shaping Gut Microbiota of Sympatric Rodent Species in a Fragmented Forest

Abstract: Gut microbiota play a significant role for animals to adapt to the changing environment. Host species and habitats are key drivers in shaping the diversity and composition of the microbiota, but the determinants of composition of the sympatric host gut microbiome remain poorly understood within an ecosystem. In this study, we examined the effects of habitats of different succession stages and host species on the diversity and composition of fecal gut microbiota in four sympatric rodent species (Apodemus draco,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 76 publications
(95 reference statements)
0
9
1
Order By: Relevance
“…Our study contributes to bridging this gap by showing that degradation of the host habitat through land-use changes can indeed induce a shift in the composition of microbial communities, and even have a positive effect, on the overall bacterial species richness associated with insects. This is in clear contradiction with our original expectations that degradation of the host habitat would also be detrimental to their associated microbial diversity and functionality (McManus et al 2021, Teng et al 2022). One possible explanation for these results is that habitat degradation in the Åland meadow network is not strong enough to lead to microbial erosion in the insect species studied.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Our study contributes to bridging this gap by showing that degradation of the host habitat through land-use changes can indeed induce a shift in the composition of microbial communities, and even have a positive effect, on the overall bacterial species richness associated with insects. This is in clear contradiction with our original expectations that degradation of the host habitat would also be detrimental to their associated microbial diversity and functionality (McManus et al 2021, Teng et al 2022). One possible explanation for these results is that habitat degradation in the Åland meadow network is not strong enough to lead to microbial erosion in the insect species studied.…”
Section: Discussioncontrasting
confidence: 97%
“…For many species, the composition of the microbiota, and especially that of the gut microbiota, is representative of their diet (McManus et al 2021). Recently, Teng et al (2022) suggested that differences in the gut microbiota associated with populations from three rodent species were linked to changes in diets between populations. The animals from farmlands, where food diversity is high, hosted the most species- rich microbiota (Teng et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies that investigated GM variations within host communities led to incongruent patterns with either a stronger impact of host phylogeny over habitats on GM assembly (e.g. Knowles et al, 2019) or the opposite (Teng et al, 2022). Therefore, gathering more data on the relationships between urbanization, host community assembly and their GM remains critical in the domain of urban ecology (Verrelli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%